2004
DOI: 10.1002/eji.200324683
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of α‐Gal on primary human endothelium does not confer susceptibility to NK cell cytotoxicity or increased NK cell adhesion

Abstract: The contribution of Gal § 1,3Gal ( § -Gal) to cell-mediated organ xenograft rejection is controversial. We have used recombinant lentiviruses encoding a porcine § 1,3 galactosyltransferase ( § 1,3GalT) to obtain § -Gal-expressing primary human aortic endothelial cells (HAEC) at a frequency of 70-90%. These cells were compared to non-transduced and mock-transduced HAEC with regard to their susceptibility to human NK cell-mediated lysis, ability to stimulate IFN-+ production by NK cells, and support of NK cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
6
24
0
Order By: Relevance
“…Therefore, we conclude that there is no direct correlation between the absence of ␣Gal and VCAM-1 and that ␣Gal does not play a crucial role in the adhesion process. In line with our findings, naive human NK cells adhered, activated, and lysed pEC independently of ␣Gal (62), and no differences regarding NK adhesion and lysis were observed upon introduction of ␣Gal in human aortic endothelial cells (63). In contrast, using ␣1,3GT-transfected COS-7 cells, soluble carbohydrates, and F(abЈ) 2 of xenoreactive NAb, Inverardi et al (37) showed a role for ␣Gal in Ab-independent NK adhesion to and destruction of pEC.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we conclude that there is no direct correlation between the absence of ␣Gal and VCAM-1 and that ␣Gal does not play a crucial role in the adhesion process. In line with our findings, naive human NK cells adhered, activated, and lysed pEC independently of ␣Gal (62), and no differences regarding NK adhesion and lysis were observed upon introduction of ␣Gal in human aortic endothelial cells (63). In contrast, using ␣1,3GT-transfected COS-7 cells, soluble carbohydrates, and F(abЈ) 2 of xenoreactive NAb, Inverardi et al (37) showed a role for ␣Gal in Ab-independent NK adhesion to and destruction of pEC.…”
Section: Discussionsupporting
confidence: 90%
“…17 For transduction, FACS-sorted cells were transferred to 10-mL tubes with 1-mL culture medium and were incubated with concentrated pHRЈEF1␣ GFPSIN virions at a multiplicity of infection (MOI) of 0.1 at 37°C in a 5% CO 2 atmosphere overnight. After virus incubation, cells were washed once in PBS and were directly injected in the denuded femoral artery of nude mice (see "Mice").…”
Section: Lentiviral Transduction Of Facs-sorted Cd14 ؉ /Vegfr-2 ؉ Andmentioning
confidence: 99%
“…Gal on porcine EC constitutes potential binding sites for human PMN, NK cells, and monocytes. Human NK cells may induce porcine EC activation by direct interaction in the absence of Gal (24,25) and no significant reduction of direct NK cytotoxicity or NK cell and PMN adhesion on porcine ECs was found in the absence of, or upon blocking, Gal. In contrast, monocyte adhesion to porcine ECs depends on Gal-mediated activation (26).…”
mentioning
confidence: 90%